Capital markets and the costs of climate policies - Marian Leimbach; Nico Bauer (Environmental Economics and Policy Studies, 2021)
Globalization is accompanied by increasing current account imbalances. They can undermine the positive impacts of increasing international cooperation and trade on economic growth and income convergence. At the same time, climate change challenges the global community and requests for co-operative action. Regional energy transformation due to climate policies and the resulting regional mitigation costs are key variables of climate economic analysis. This study is the first that include current account imbalances and imperfect capital markets to investigate potential market feedback mechanisms between climate policies, energy sector transformation and capital markets. Furthermore, it answers the question whether the capital-intensive transformation towards zero-carbon economies increases the policy cost of mitigation under the condition of imperfect capital markets. First results demonstrate a dominant baseline effect of capital market imperfections on macroeconomic variables, and moderate effects on mitigation costs in global climate policy scenarios. For some regions (e.g. Middle East) estimates of relatively high mitigation costs are revised downwards, if imperfect capital markets are considered.
Keywords: 330; Capital flows; Climate policy; Current account; Economic growth model; International trade; Lucas Paradox; Mitigation costs